2007
DOI: 10.1016/j.ijgo.2007.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial volume as predictor of malignancy in women with postmenopausal bleeding

Abstract: An endometrial volume of 1.35 mL or greater may predict malignancy in women with postmenopausal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…23 However, these authors reported that the best cutoff for endometrial volume was 1.35 ml with a sensitivity of 100% and a false-positive rate of 29%, much higher than that reported by Gruboeck. An explanation for that is that Mansour's study included patients with 'endometrial atypia' in the group of endometrial cancer.…”
Section: Endometrial Cancermentioning
confidence: 79%
“…23 However, these authors reported that the best cutoff for endometrial volume was 1.35 ml with a sensitivity of 100% and a false-positive rate of 29%, much higher than that reported by Gruboeck. An explanation for that is that Mansour's study included patients with 'endometrial atypia' in the group of endometrial cancer.…”
Section: Endometrial Cancermentioning
confidence: 79%
“…16 There is no good screening test for endometrial carcinoma. However, transvaginal ultrasound to detect endometrial thickness 17 and measurement of endometrial volume 18 can be used to predict malignancy. The peak age of endometrial carcinoma is between 56 to 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial volume is measured using virtual organ computer-aided analysis (VOCAL) or a similar software. Studies have shown that EV is a better predictor of endometrial cancer than ET [39][40][41]. However, each study has defined a different cut-off value for EV, ranging between 1.35 and 3.56 ml.…”
Section: Oncologymentioning
confidence: 99%